National and Energy Security in Terms of Human Development - Bjegović, Miroslav; Radovanović, Mirjana; Župac, Goran (Industrija, 2018)
Governing energy is one of the main challenges for the secure global future. Energy security is integral part of national security system, characterized by strong causal relationship with economic, social and geopolitical movements as a whole. Regardless of the high significance, there are major challenges in defining methodologies for control of the governance in this area. In addition, results of control measurements could be (miss)interpreted and/or intentionally created for certain geopolitical purposes. Methodology analysis, which will be presented in this paper, is Energy Trilemma Index, developed by distinguished World Energy Council. Main objective of this paper is assessment of reliability of this Index, which is done by testing of its methodological concept itself on the sample of 33 countries. Analysis is conducted by review of available reports, general descriptive statistics and data processing. Spearman’s rank-order correlation test has been applied to four main variables: three variables - constituents of Energy Trilemma Index and Human Development Index as control variable. Results of this research point to the significant shortcomings of Index itself, because of which it is recommended for all the regulation, strategies and assessments done and/or supported by use of Energy Trilemma Index to be taken with certain level of caution.